Penerapan Metode Demonstrasi Untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran PPKn VIII MTs Anwar Futuhiyyah - Fatmawati, Fifi; Kurnia, Heri (Jurnal Pendidikan Kewarganegaraan dan Politik, 2025)
Improving student learning outcomes is a primary goal in the context of education. Effective teaching methods can be key to achieving these goals. One method that can be applied is the demonstration method. The purpose of this study was to explore the application of the demonstration method and its impact on student learning outcomes. The demonstration method is a teaching strategy that involves the use of direct examples, modeling, or practical displays of concepts or skills being taught. In this study, the demonstration method was applied in a classroom environment to facilitate student understanding and improve their learning outcomes. This study used a classroom action research (CAR) approach that should involve teachers and students in the research process. However, here this study only involved teachers, because students had already taken the Final Semester Exam. Data were collected through observation and interviews with PPKN subject teachers. The results showed that the application of the demonstration method had a positive impact on student learning outcomes. The application of the demonstration method allows students to see and experience the concepts or skills being taught directly. This allows students to develop a better understanding and strengthen their skills through observation and active participation.